Keberlanjutan Blue Bonds di Indonesia: Peluang dan Risiko - Julian Halim, Evelyne (UNES Law Review, 2023)
Indonesia is a maritime country with around 71 percent of Indonesia’s territory being sea. Indonesia’s marine potential is estimated to support more than USD 180 billion of economic activity annually. The blue economy or also called “marine economy” is a concept for protecting the sea, marine and aquatic resources. There are a number of financing mechanisms that encourage the blue economy, namely blue bonds, debt-for-nature-swap, blue IPO, blue financing and etc. Blue bond are debt instruments that finance the protection of important clean water resources as well as ocean and marine-based projects with positive environmental and social benefits. Blue bonds are part of thematic bonds where the proceeds from the bonds are used to finance sustainable development projects. The research method used is doctrinal research with approach used being a conceptual approach and a statutory approach. Indonesia issued its first blue bond in May 2023. The blue bond was issued using the Green Bond Principle issued by the International Capital Market Association. This blue bond issuance refers to POJK No. 60/2017. POJK No. 60/2017 has been revised with POJK No. 18 of 2023. On POJK No. 18 of 2023, there is no definition of blue bond and the KUBL category which covers the types activities in blue bond comprehensively. There are no technical criteria that determine whether a project is truly a “blue” project or “blue” standard criteria in Indonesia. This is vulnerable to misuse by companies, which can increase the risk of blue-washing.